2020
DOI: 10.3390/healthcare8040396
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceived Social Support in Assessing Posttraumatic Stress Disorder and Mental Health-Related Quality of Life in Veterans

Abstract: This study aims to establish the effect of self-perceived social support on the intensity of Post-Traumatic Stress Disorder (PTSD) symptoms and Mental Health-Related Quality of Life (MHRQoL) in veterans more than two decades after exposure to trauma in the Homeland War in Croatia, which took place from 1990 to 1995. The sample comprised 259 Croatian Homeland War veterans diagnosed with PTSD, with at least 6 months of combat experience. Among them, 90 subjects had also experienced imprisonment in enemy prison c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In addition to a younger age, lower levels of education and lack of social support were also significant predictors of depression several decades after the war in a study that included prisoners from both World War II and the Korean War [21]. Other studies have also shown that lack of social support is one of the most significant predictors of developing PTSD and other psychological disorders [49,[77][78][79][80].…”
Section: Personality Vulnerability Socio-demographic Factors and Soci...mentioning
confidence: 97%
“…In addition to a younger age, lower levels of education and lack of social support were also significant predictors of depression several decades after the war in a study that included prisoners from both World War II and the Korean War [21]. Other studies have also shown that lack of social support is one of the most significant predictors of developing PTSD and other psychological disorders [49,[77][78][79][80].…”
Section: Personality Vulnerability Socio-demographic Factors and Soci...mentioning
confidence: 97%
“…Specially, a study has shown that after leaving the war zone, veterans who had a more positive view of being supported after coming from the battlefield had less intense PTSD symptoms and better mental health and quality of life than did those who did not (Jukic, 2020).…”
Section: Soc Pss On Ptsdmentioning
confidence: 99%
“…It has been described that war times, post war, or natural disasters, lead to biopsychosocial issues and have an impact on the quality of life (QoL) of those who go through such events [25][26][27][28][29]. However, research on the impact of collective violence on health has been scarce and relatively disciplinary fragmented and has not considered all aspects of human beings.…”
Section: Introductionmentioning
confidence: 99%